Methadone-Induced Toxic Brain Damage. (22nd May 2013) - Corré, Jérôme; Pillot, Jérôme; Hilbert, Gilles
Abstract : A 29-year-old man presented with comatose after methadone intoxication. Cerebral tomography only showed cortico-subcortical hypodense signal in the right cerebellar hemisphere. Brain MRI showed a rare imaging of FLAIR and DWI hyperintensities in the two cerebellar hemispheres as well as basal ganglia (globi pallidi), compatible with methadone overdose. To our knowledge this is the first reported case of both cerebellar and basal ganglia involvement in methadone overdose.